A multi-sample investigation of the higher-order latent dimensionality of the Sport-Multidimensional Perfectionism Scale-2. (November 2016) - Dunn, John G.H.; Gotwals, John K.; Causgrove Dunn, Janice; Selzler, Anne-Marie; Lizmore, Michael R.; Vaartstra, Matthew; Sapieja, Klaudia M.; Gamache, Vania E.
Abstract: Objective: Examine the higher-order latent dimensionality of the Sport-Multidimensional Perfectionism Scale-2 (Sport-MPS-2: Gotwals & Dunn, 2009). Design: Correlational. Method: A total of 1605 athletes (562 female) from eight independent samples completed the Sport-MPS-2. Athletes in one sample ( n  = 239) also completed a portion of the Multidimensional Inventory of Perfectionism in Sport (MIPS: Stoeber, Otto, & Stoll, 2006). The correlation matrices among the Sport-MPS-2 subscales for five samples were analyzed with exploratory factor analyses. The covariance matrices for the subscales in the three remaining samples (including the sample that completed the MIPS) were analyzed with confirmatory factor analyses and exploratory structural equation modeling (ESEM: Asparouhov & Muthén, 2009). Results: Two highly interpretable factors—labelled Perfectionistic Strivings and Perfectionistic Concerns —were obtained for each data set. Conclusion: Theorists note the importance of using multiple indicators to measure perfectionistic strivings and perfectionistic concerns in sport. The current factor-analytic and ESEM results indicate that the six subscales comprising the Sport-MPS-2 may help to achieve this objective. Highlights: Sport-MPS-2 subscales reflect two higher-order dimensions of perfectionism in sport. Two subscales reflect the higher-order dimension of perfectionistic strivings. Four subscales reflect the higher-order dimension of perfectionistic concerns. The Sport-MPS-2 provides multiple indicators of strivings and concerns in sport.